Analyzing the Effects of Inflation on Consumer Purchasing Behavior in Emerging Markets - Anna Audty; Lucas Meyer (International Journal of Economics, Commerce, and Management, 2024)
This article explores how inflation affects consumer purchasing behavior in emerging markets. Through a combination of qualitative and quantitative research methods, the study examines changes in spending habits, preferences for goods, and brand loyalty during periods of high inflation. The findings highlight the adaptive strategies consumers employ to manage their purchasing decisions and the implications for marketers in these economies.